The Synarcual of the Little Skate, Leucoraja erinacea: Novel Development Among the Vertebrates - Johanson, Zerina; Martin, Kyle; Fraser, Gareth; James, Katherine (Frontiers in Ecology and Evolution, 2019)
Evolutionary variation in anteroposterior patterning of the axial skeleton is a major contributor to the evolution of the vertebrate body plan, with five canonical vertebral types in tetrapods (cervical, thoracic, lumbar, sacral, caudal). However, less is known about the evolutionary origin and variation in vertebral regionalization patterns outside of tetrapods where described vertebral types range from as few as two in some chondrichthyans to eight or more in some teleost fishes. The synarcual is a specialized adaptation of the anterior axial skeleton comprising a putatively fused array of vertebral elements characteristic of jawed vertebrate (gnathostome) clades such as batoid and chimaeroid chondrichthyans where they support enlarged pectoral fins and dorsal fin spines respectively, as well as a fossil group known as the placoderms. Placoderms represent the phylogenetically most basal jawed vertebrates and the presence of a synarcual in these and chondrichthyans may suggest a conserved vertebral type for jawed vertebrates, predating the divergence of stem and crown gnathostomes. Alternatively, synarcuals may have evolved independently in these lineages, exhibiting a remarkable case of morphological convergence. In order to address this question, we investigated the early development of the cervicothoracic synarcual of an emerging model chondrichthyan: the Little skate Leucoraja erinacea. By combining x-ray computed tomography, and classical histology, we show that the skate synarcual is a complex composite element which develops from a hollow, continuous cartilaginous element devoid of any vertebral centra anterior to the pectoral girdle, and fusion/remodelling of initially distinct vertebrae posteriorly. A de novo transcriptome assembly for two developmental stages of the skate synarcual and post-synarcual axial skeletal elements supported this two-phase development, with differences in expression levels of several developmental genes, including Hox family transcription factors, which suggest anterior-posterior regionalization along the vertebral column, potentially linked to the synarcual. As well, multiple genes related to skeletal remodelling were found to be more highly expressed at stage 33, including genes related osteoclast activity, normally associated with removal of bone, a tissue absent in chondrichthyans. These genes are potentially related to loss of mineralization as vertebral elements are incorporated into the synarcual.